121 Comparison of Corn Fermented Protein (CFP) to Traditional Yeast and Distillers Grain fed to Healthy Adult Cats. (21st September 2022) - Kilburn, Logan; Aldrich, Charles G
Abstract: Co-products from the ethanol industry may be able to provide high-quality sustainable protein sources for pet foods. Unlike traditional co-products, corn fermented protein (CFP) contains a yeast component which may provide additional benefits. The objective of this study was to determine, by exchange, the effects of the yeast in corn fermented protein on diet utilization. The four experimental diets included a control with no yeast (CON) and diets containing either 3.5% brewer's dried yeast (BDY), 17.5% distiller's dried grains with solubles plus 2.5% brewer's dried yeast (BDY+DDGS), or 17.5% CFP (CFP). It was assumed that CFP contained 20% yeast and all treatments except CON were formulated to contain 3.5% yeast. Experimental diets were fed to adult cats (n = 11) in a replicated 4 x 4 Latin Square design. Cats were adapted to diet for 9 days followed by a 5-d total fecal collection. Titanium dioxide (0.4%) was added to all diets as a marker to estimate digestibility. Data were analyzed using a mixed model in SAS (version 9.4, SAS Institute, Inc., Cary, NC) with treatment as a fixed effect and cat and period as random effects. Dry fecal output of cats was greatest for BDY+DDGS at 20.2 g/d compared with the other treatments at an average of 16.3 g/d (P < 0.05). Defecations per day were also greatest for cats consuming BDY+DDGS (P < 0.05). When comparing CFP with BDY+DDGS, the digestibility of dry matter, organic matter, and gross energy was about 3% greater (P < 0.05) for CFP. Short or branched chain fatty acids in fecal samples were not altered by dietary treatment. The increase in fecal output and decrease in digestibility with BDY+DDGS indicates a greater fiber effect in the DDGS compared with the CFP. Therefore, the yeast component in CFP may be providing a greater nutrient utilization when fed to cats.